Genetic Features of Plasmid- and Chromosome-Mediated mcr-1 in Escherichia coli Isolates From Animal Organs With Lesions - Liu, Zengyuan; Liu, Yingqiu; Xi, Wei; Liu, Shuangshi; Liu, Jia; Mu, Hailong; Chen, Beibei; He, Hao; Fan, Yunpeng; Ma, Wuren; Zhang, Weimin; Fu, Mingzhe; et al. (Frontiers in Microbiology, 2021)
The mobile element adjacent to the mcr-1 gene located on plasmids has been wide-ly reported. However, less is known about the other functional regions of plasmids containing the mcr-1 gene. The present study investigated the diversity of sequence type (ST) and the features of mcr-1-carrying plasmids in Escherichia coli (E. coli) from animals with reduced effectiveness to antimicrobial. 24 mcr-1-positive E. coli isolates (MPEC) in our study showed both multidrug resistance and extensively drug resistance. The predominant clonal complexes (CC) mainly belonged to CC156, CC448, and CC10. Among the sequence types, ST10596 was a new-ly-discovered one isolated from swine. The mcr-1 genes of five representative strains were located on chromosome (J-8), IncX4-(S-4), IncI2-(19-5, J-9) and In-cHI2/HI2A/N-type (A-3) plasmid. With the loss of the flanking ISApl1, four mcr-1 genes were successfully transferred to recipients and embedded in mcr-1-pap2 cas-settes located on the plasmids, whereas for the chromosome, the gene was embed-ded in Tn6330. Furthermore, the virB6 gene in T4SS on the IncX4-type plasmid pS4-mcr-1.1 was truncated by IS2 while stbD and stbE genes, encoding the plasmid stability protein on IncI2-type plasmid pMCR_J9_7, was missing. TraI gene in T4SS on the IncHI2/HI2A/N-type hybrid plasmid pMCR_A3_2 was also truncated by IS100. For the MDR region, two class 1 integrons (In0, In640) and four compo-site transposons (Tn4352, Tn6010, cn_4692_IS26, cn_6354_IS26) were identified. All the 24 MPECs exhibited population diversity, with the loss of the ISApl1 trans-poson element in mcr-1-carrying plasmids being more beneficial to stabilize the mcr-1 gene under the pressure of antimicrobial agents. Similarly, the IS, Tn, In el-ements on the plasmid are beneficial for the mobilization of antibiotics resistance genes (ARGs) but they may also affect the conjugative transfer ability of the plas-mids due to the insertion/deletion of genes in the conjugative transfer region.